Распространенность стоматологических заболеваний, требующих ортопедического лечения, среди работников завода «Днепроспецсталь» - Возная, И. В.; Самойленко, А. В.; Samoilenko, A. V.; Vozna, I. V. (My University, 2019)
Цель. Изучить распространенность стоматоло-гических заболеваний, требующих ортопедического лечения у работников завода «Днепроспецсталь» г. Запорожье. Материалы и методы. Проведено обследование 913 работников: 675 (73,9%) мужчин и 238 (26,1%) женщин. Осмотренные были разделены на четыре возрастные группы. The aim of the study. To carry out the analysis of the dental diseases prevalence requiring orthopedic treatment among the employees of the “Dniprospetsstal” plant in Zaporizhzhya. Materials and methods. In order to study the dental diseases prevalence requiring orthopedic treatment, we’ve examined 913 employees among the Zaporizhzhya “Dniprospetsstal” plant workers: 675 (73.9%) men and 238 (26.1%) women. All examined were divided into four age groups: the 1st (21-30 years) - 145; the 2nd (31-40 years) - 270; the 3rd (41-50 years) - 278; the 4th (51-60 years) - 220 employees.
Prevalence of dental diseases requiring orthopedic treatment in Dniprospetsstal employees
Keywords: стоматологические заболевания; потребность в протезировании; распространенность; Prevalence; dental diseases; need in prosthetics